Genome- and Transcriptome-Wide Identification of C3Hs in Common Bean (Phaseolus vulgaris L.) and Structural and Expression-Based Analyses of Their Functions During the Sprout Stage Under Salt-Stress Conditions - Zhang, Qi; Zhang, Wen-jing; Yin, Zhen-gong; Li, Wei-jia; Zhao, Hao-hao; Zhang, Shuo; Zhuang, Lin; Wang, Yu-xin; Zhang, Wen-Hui; Du, Ji-Dao (Frontiers in Genetics, 2020)
CCCH (C3H) zinc-finger proteins are involved in plant biotic and abiotic stress responses, growth and development, and disease resistance. However, studies on C3H genes in Phaseolus vulgaris L. (common bean) are limited. Here, 29 protein-encoding C3H genes, located on 11 different chromosomes, were identified in P. vulgaris. A phylogenetic analysis categorized the PvC3Hs into seven subfamilies on the basis of distinct features, such as exon–intron structure, cis-regulatory elements, and MEME motifs. A collinearity analysis revealed connections among the PvC3Hs in the same and different species. The PvC3H genes showed tissue-specific expression patterns during the sprout stage, as assessed by real-time quantitative PCR (RT-qPCR). Using RNA-sequencing and RT-qPCR data, PvC3Hs were identified as being enriched through Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses in binding, channel activity, and the spliceosome pathway. These results provide useful information and a rich resource that can be exploited to functionally characterize and understand PvC3Hs. These PvC3Hs, especially those enriched in binding, channel activity, and the spliceosome pathway will further facilitate the molecular breeding of common bean and provide insights into the correlations between PvC3Hs and salt-stress responses during the sprout stage.